Modalitas Pencitraan Non Invasif pada Sindroma Koroner Kronis - Indrihapsari, Pratiwi; Widito, Sasmojo (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Advancements in non-invasive cardiovascular imaging technology have introduced robust diagnostic modalities for managing cardiovascular diseases. Three prominent techniques in this domain are stress echocardiography, coronary computed tomography angiography (CCTA), cardiac magnetic resonance imaging (CMR), Single Photon Emission Computed Tomography (SPECT), and Positron Emission Tomography (PET). These modalities provide crucial information for accurate diagnosis and optimal therapeutic planning. Stress echocardiography occupies a strategic position in the diagnostic algorithm, particularly in suspected or confirmed cases of coronary artery disease. The strength of this modality lies in its ability to provide a comprehensive picture of myocardial functional status. Meanwhile, CCTA offers superiority in visualizing and characterizing atherosclerotic plaques in coronary vessels, enabling early detection and more precise risk stratification. This literature review aims to explore critical aspects of non-invasive cardiovascular imaging modalities in the context of diagnosing Chronic Coronary Syndrome.